A Narrative Review on Clinical and Experimental Evidence of Shatavari Ghrut - Ashvini Deshmukh (Paradkar); Anita Wanjari (Journal of Clinical and Diagnostic Research)
Ayurvedic dosage forms possess unique characteristics in both formulation and therapeutic applications. Sneha Kalpana encompasses a range of medicated oils and ghee-based products, which are effectively used to treat a diverse array of ailments across various age demographics. On the other hand, the liposomal drug delivery system represents a modern advancement in traditional medicine. Shatavari Ghrut (SG) is a notable formulation that falls under the category of Ghrut Kalpana in Ayurveda. There are numerous references to SG in Ayurvedic classics for various diseases. It is fascinating to observe the wide range of applications and the growing interest in the efficacy of SG through clinical and preclinical studies. Narrative reviews play a crucial role in summarising existing evidence and identifying gaps in knowledge for further exploration. Here’s an outline of the potential therapeutic uses and the importance of narrative reviews in evaluating SG. Relevant sources include Ayurvedic texts and scientific databases such as Pubmed, Scopus, Ayush Research Portal, ResearchGate, Digital Helpline for Ayurveda Research Articles (DHARA), Cochrane, Shodhganga, and Google Scholar, using keywords like Asparagus racemosus Wild, clinical studies on Shatavari Ghrut, lipid preparations of Shatavari, preclinical studies on Shatavari Ghrut, and Shatavari as a key.